Radiological study of the myriad variations in frontal sinus anatomy: an institutional study - Vepamininti, Sreenivas; Seetharam, Soumya M.; George, Jomy; Vamanshankar, Hemanth; Saidha, Poonam K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The frontal sinus is a challenging area for endoscopic surgeons. The variations in the frontal sinus differs so much among individuals that there are forensic applications. A detailed radiological study of the sinus is important for understanding the pathophysiology of sinusitis and as a prerequisite for frontal sinus drainage procedures. Aims and objectives were to document the anatomical variations of the frontal sinus (radiological) and to correlate the variations with the signs and symptoms of sinusitis. Methods: Coronal and axial CT paranasal sinuses scans of 30 consecutive patients who attended the Otolaryngology clinic OPD in St. John’s medical college and hospital, Bangalore, India with signs/symptoms of chronic sinusitis were evaluated between January to July 2018. Results: The average frontal sinus diameter in patients with sinusitis was 6.65 mm. The prevalence of frontal cells in our study was 48%. Agger nasi cells were the most common cells seen. Frontal sinus disease was found in 72% of the studied sides in the scans. Conclusions: Frontal sinus anatomy varies with different ethnicities. It is very important to study the frontal sinus anatomy before exploring the sinus for disease clearance and avoid surgical complications.